ANALISIS PERSEDIAAN KEMASAN DRUM STEEL MENGGUNAKAN METODE JUST IN TIME DI PT. TUNAS SUMBER IDEA KREASI KIMIA - Maftuhi; Sulistyo, Arif Budi (Universitas Majalengka, 2024)
PT Tunas Sumber Idea Kreasi Kimia is a company engaged in chemical production, such as alkyd resin, amino resin, acrylic resin and latex emulsion. The purpose of this study is to overcome the excess inventory of steel drum type packaging which causes losses because there are inventory costs consisting of purchase costs, ordering costs and storage costs. The method used in this research is the Just in Time (JIT) method. The results showed that the Just in Time (JIT) method obtained an inventory cost of Rp. 5,244,056,000 which is 10% more efficient than the calculation results according to company policy which obtained an inventory cost of Rp. 5,816,152,000 or a savings of Rp. 572,096,000. So that the Just in Time method can be applied at PT Tunas Sumber Idea Kreasi Kimia to save on inventory costs and improve the company's operational efficiency.